Ejector expansion refrigeration system: Ejector design and performance evaluation. (October 2015) - Hassanain, M.; Elgendy, E.; Fatouh, M.
Abstract: Use of a two-phase flow ejector as an expansion device in vapor compression refrigeration systems is one of the efficient ways to enhance its performance. The present work aims to design a constant-area two phase flow ejector and to evaluate performance characteristics of the ejector expansion refrigeration system working with R134a. In order to achieve these objectives, a simulation program is developed and effects of operating conditions and ejector internal efficiencies on the system performance are investigated using EES software. Comparison between present results and published experimental data revealed that the developed model can predict the system COP with a maximum error of 2.3%. The system COP increased by 87.5% as evaporation temperature changed from −10 °C to 10 °C. Finally, correlations to size ejector main diameters as a function of operating conditions, system cooling capacity and ejector internal efficiencies are reported. Highlights: Design of constant-area ejector and EERS performance characteristic are investigated. The developed model can predict the system COP with a maximum error of 2.3%. System cooling capacity has the most significant impact on the ejector design. Ejector internal efficiencies have insignificant impact on system COP. Suction nozzle exit diameter was the most influenced by the ejector internal efficiencies.